2013
DOI: 10.1002/maco.201206985
|View full text |Cite
|
Sign up to set email alerts
|

Passivation of HAZs of APIX100 pipeline steel in bicarbonate‐carbonate solutions at 298 K

Abstract: This research explores electrochemical correlations between heat‐affected zones (HAZs), produced by Gleeble© thermal simulation cycles, and their passivation behavior in bicarbonate–carbonate solutions. The investigations were carried out in comparison with the base API‐X100 steel in naturally aerated 0.5 g/L chloride solutions, containing a matrix of bicarbonate and carbonate concentrations at 298 K. The slow 0.05 mV/s potentiodynamic scans revealed that the passivation onsets earlier in proportion with the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…3, were monitored for 20 000 s to analyse the significance of the bicarbonate concentration with the interfacial interactions and passivation. In de-oxygenated solutions, bicarbonate, besides water and hydroxyl, drives both the anodic and cathodic reactions without interference from oxygen, 11 carbonate, 28 or H 2 CO 3 . 29 During free immersion, bicarbonate adsorbs onto the surface and raises the local alkalinity (the concentrations of hydroxyl which is of direct anodic roles).…”
Section: Resultsmentioning
confidence: 99%
“…3, were monitored for 20 000 s to analyse the significance of the bicarbonate concentration with the interfacial interactions and passivation. In de-oxygenated solutions, bicarbonate, besides water and hydroxyl, drives both the anodic and cathodic reactions without interference from oxygen, 11 carbonate, 28 or H 2 CO 3 . 29 During free immersion, bicarbonate adsorbs onto the surface and raises the local alkalinity (the concentrations of hydroxyl which is of direct anodic roles).…”
Section: Resultsmentioning
confidence: 99%
“…The cyclic voltammetry started at À1.1 V versus SCE, during which water was reduced under charge-transfer control (Eq 2) ( Ref 1,8,10), producing hydrogen and hydroxyl ions, as depicted in Fig. 2.…”
Section: Cathodic Reduction Reactionsmentioning
confidence: 99%
“…It might not have fully consolidated some of the mechanistic details that are until today being investigated, but it provides a visual guide that helps better understand the corrosion reactions and the significance of the properties and reactivity of the corrosion products. The test samples are made of API-X100, a new-generation pipeline steel, whose electrochemical significance and behavior were explained and examined previously ( Ref 1,8,10,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on the corrosion behavior of the carbon steel in NaHCO 3 solution saturated with CO 2 have reported that the carbon steel is passive in NaHCO 3 solution; however, no consensus on passivation mechanism has been reached. Therefore, in the present study, a thin wire specimen with a small working area was used.…”
Section: Introductionmentioning
confidence: 99%